COVID-19, Poverty, and Social Safety Net Response in Zambia - Paul, Boban Varghese; Finn, Arden; Chaudhary, Sarang; Mayer Gukovas, Renata; Sundaram, Ramya (World Bank, Washington, DC, 2021)
What has the impact of the COVID-19 pandemic been on poverty in Zambia, and how can social protection programs mitigate these effects? This paper estimates the pre-pandemic poverty level in Zambia and then simulates the distributional impact of COVID-19 in the country. The paper also estimates the impact of a social cash transfer program that led the COVID response, on poverty levels. In the absence of recent nationally representative household survey data, this is done by updating the consumption distribution in the 2015 Living Conditions Monitoring Survey using annual real per capita gross domestic product growth rates for specific sectors. The study shows that the national poverty headcount rate increased from 54.4 percent in 2015 to 55.8 percent in 2019, and this change was driven entirely by rural areas. By contrast, the economic impact of COVID-19 has disproportionately impacted urban areas and exacerbated the already high poverty levels, with the poverty headcount increasing to 57.6 percent in 2020. Expanding and enhancing cash transfers have been a key policy lever that many countries have used to mitigate the negative economic consequences of the pandemic. Simulations in Zambia suggest that a fully operational social cash transfer program with the current and proposed enhanced transfer amounts has the potential to reduce poverty significantly – by four and six percentage points, respectively. Beyond this specific analysis, the paper makes a case for the innovative use of existing data to inform adaptive or shock responsive social protection, even in largely data poor environments.